Applying of Cooperative Integrated Reading and Composition (CIRC) Strategy on Students’ Reading Comprehension - Umar Al Faruq A Hasyim; Yeasy Agustina Sari; Nurul Puspita (CV. Creative Tugu Pena, 2020)
The article was to analyse Cooperative Integrated Reading and Composition (CIRC) Strategy Effective on student’s reading comprehensio, especially in recount text. This research was conducted at tenth grade in second semester at tenth grade SMA 10 Bandar Lampung The design of this research was quantitative research. The subject of this research was 32 students at tenth grade of SMA 10 Bandar Lampung. The result of the research showed that the significant influence was clarified by the assumption of the level of the coefficients correlation between Cooperative Integrated Reading and Composition (CIRC) Strategy and students’ reading comprehension which was signing positive. Directing to positive correlation means that if the level of Cooperative Integrated Reading and Composition (CIRC) Strategy is high, the level of students’ reading comprehension is also high. In contrast, if the level of Cooperative Integrated Reading and Composition (CIRC) Strategy is low, the level of students’ reading comprehension is also low. Moreover, based on the result of hypothesis testing result (table of correlations) demonstrated that r observed is higher than r table with N = 32, it can be looked at significant either for level 5 % or 1 %. In the table also demonstrated that the level of significant was 1,696 < 10,56 > 2,040. It means that the correlation between Cooperative Integrated Reading and Composition (CIRC) Strategy and students’ reading comprehension was significant. Keyword: Reading Comprehension, CIRC Strategy, Reading and Composition (CIRC) Strategy